Regional Patterns of Sea Surface Temperature Change: A Source of Uncertainty in Future Projections of Precipitation and Atmospheric Circulation - Ma, Jian; Xie, Shang-Ping (Journal of climate, 2013)
Precipitation change in response to global warming has profound impacts on environment for life but is highly uncertain. Effects of sea surface temperature (SST) warming on the response of rainfall and atmospheric overturning circulation are investigated using Coupled Model Intercomparison Project simulations. The SST warming is decomposed into a spatially uniform SST increase (SUSI) and deviations from it. The SST pattern effect is found to be important in explaining both the multimodel ensemble mean distribution and intermodel variability of rainfall change over tropical oceans. In the ensemble mean, the annual rainfall change follows a “warmer-get-wetter” pattern, increasing where the SST warming exceeds the tropical mean, and vice versa. Two SST patterns stand out both in the ensemble mean and intermodel variability: an equatorial peak anchoring a local precipitation increase and a meridional dipole mode with increased rainfall and weakened trade winds over the warmer hemisphere. These two modes of intermodel variability in SST account for one-third of intermodel spread in rainfall projection. The SST patterns can explain up to four-fifths of the intermodel variability in intensity changes of overturning circulations. SUSI causes both the Hadley and Walker circulations to slow down, as articulated by previous studies. The weakening of the Walker circulation is robust across models as the SST pattern effect is weak. The Hadley circulation change, by contrast, is significantly affected by SST warming patterns. As a result, near and south of the equator, the Hadley circulation strength change is weak in the multimodel ensemble mean and subject to large intermodel variability due to the differences in SST warming patterns.